Synergetic recognition and separation of kelthane and pyridaben base on magnetic molecularly imprinted polymer nanospheres. Issue 20 (6th October 2016) - Li, Shuhuai; Xu, Mingze; Wu, Xuejin; Luo, Jinhui
Abstract : We present novel magnetic composite nanospheres for the preparation of a nanoiron oxide/carbon dots/β‐cyclodextrin/molecularly imprinted polymer for the selective solid‐phase extraction kelthane and pyridaben from vegetables. The molecularly imprinted polymer was synthesized on the surface of nano‐iron oxide/carbon dots via a chemical polymerization procedure, where kelthane‐β‐cyclodextrin and pyridaben‐β‐cyclodextrin inclusion complexes were used as template molecules, and their adsorption behavior was investigated in detail. Characterization analysis and binding experiments revealed that magnetic composite nanospheres had outstanding magnetic properties, a large adsorption capacity, and high competitive selectivity for kelthane and pyridaben. The magnetic composite nanospheres were employed as an adsorbent in solid‐phase extraction for the determination of kelthane and pyridaben in vegetable samples. The recoveries of kelthane and pyridaben were 92.8–105.2 and 94.4–104.6%, respectively.